FORMATION OF PUPILS' MUSIC LEARNING EXPERIENCE AND SELF-EXPRESSION SKILLS IN SOCIO-EMOTIONAL ACTIVITIES - Kepule, Iveta; Strode, Aina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
When emphasizing a role of education in development of creative personality, attention during the process of teaching music is paid to the pupil’s social and emotional learning which determines formation of self-expression skills based on the pupil’s attitude and personal qualities. Emotions as one of the main mechanisms of mental activity and behavior are directed toward satisfaction of current needs, while social processes determine a way how a pupil assesses intensity of the motivation establishing emotional stimulus. The motivation area of the self-expression formation in teaching music is determined by the social and emotional learning environment of the pupil, facilitating interaction of emotional and cognitive processes, and formation of mutual relationships in family, class, school and among peers. The aim of the study: to characterize the types of social and emotional activity facilitating self-expression of pupils in teaching music, their correlation with the self-expression of the pupil’s personality in social environment. Research methods: analysis of scientific literature, analysis of the author’s teaching experience, thematic analysis of the pupil’s essays in emotional and social context.